Собачья работа: [роман] / Л. Н. Пучков - Пучков Лев Николаевич (Черная кошка, 1998)
Экземпляры: ф.12 (ретро) / Инвентарный номер: 34369 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 90 / ББК: 84(2Рос=Рус)6